ONTOLOGI ILMU PENGETAHUAN PERSPEKTIF ISLAM (Hirarki Wujud Menurut Al-Farabi dan Perbandingannya dengan Barat) - Saeful Bahri; Alip Toto Handoko; Ahmad Faqih Udin (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2024)
The ontological foundations of science in the western and Islamic views have differences. This has an impact on different classifications of science. One of the Muslim philosophers who classified science was al-Farabi. This article aims to review or explain the ontological foundations of Science in Islamic and Western views, and the herarchy of existence according to al-Farabi. The study in this study uses qualitative methods, the source of data is in the form of ideas from Al-Farabi, which are obtained from secondary sources in the form of books, journals, and scientific articles. Based on the results of this research, it was revealed that in the Islamic view ontological studies are not only limited to physical-empirical matters so that the classification of science according to al-Farabi includes all parts of both the physical and metaphysical fields. One of the important points of the classification of sciences according to al-Farabi's view is that he has classified sciences that depart from the division of the hierarchy of maujudat (ontological status) at 4 (four) levels, namely: Allah, as obligatory al-being, then angels, celestial bodies (celestial) and earth bodies (terrestrial). Keywords : Ontology, Science, Hierarchy, Al-farabi